ANALISIS GENDER: PERAN GANDA ISTRI PEKERJA BURUH HARIAN DI PERKEBUNAN SAWIT UNTUK MEMENUHI KEBUTUHAN KELUARGA DALAM PERSPEKTIF EKONOMI ISLAM (STUDI DESKRIPTIF PADA PT. LONDON SUMATERA, TRANS SUBUR MUARA LAKITAN, MUSI RAWAS) - Melis Melis (An Nisa'a, 2018)
The wife's role in the household at this time has shifted out of the house, in the sense that the wife is out of the house to work to help her husband. The phenomenon of women's role and contribution to work is very large can be seen from the spirit of the wives at work. In a gender perspective this is justified. Wives in the village of Trans Subur SP. 2 most of them work as day laborers by "stopping" oil palm in PT. Lonsum. Such conditions make women have two peram at the same time that is the domestic role in charge of managing the household and the role of the public who work outside the home or work to improve family welfare. The problem in this research is how is the dual role of the wife who works as a daily laborer in fulfilling the needs of the family in a gender perspective? What is Islamic economic theory about the division of labor in conjugal gender relations? and How does the Islamic economy view a wife who works to meet family needs? The purpose of this study was to analyze the dual roles of wives of oil palm daily laborers in meeting the family needs of a gender perspective, knowing the division of labor in conjugal relations in the perspective of Islamic economics, and analyzing Islamic economic perspectives on the role of a wife who works to meet family needs. This study uses qualitative descriptive methods collected in the form of images, words, photographs and other notes. The method of data collection carried out in research is by observation, interviews, and analyzing data using two data, namely primary data and secondary data. The results of this study show that the role of women is very important. Women are able to help their husbands in meeting their daily needs in their families. Women are able to play a role both in the household and also in the external environment, namely the education, health, economic and social sectors. By working the wife automatically the role of the wife becomes a double, namely being a housewife and as a female worker. From the aspect of Islamic economics, it is clear that Islamic teachings allow women to work. It's just that he must understand his main task at home, serving his husband and children. After that he can do work outside the home.